2012
DOI: 10.1111/fcsr.12002
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Immigrant Families and Christian Faith Community: A Qualitative Study

Abstract: Like most other immigrants, Chinese immigrants in the U.S. have experienced challenges in acculturation to the American mainstream culture. Major challenges for Chinese immigrants include identity problems, language barriers, relationships problems, and lack of economic and social resources (Families and change: Coping with stressful events and transitions (pp. 307–332). New York: Sage). With respect to social resources, the Chinese Christian Church plays an important role in coping, acculturation, and assimil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…(Brown, Lu, Marks, & Dollahite, ; Chaney et al, ; Dollahite, & Marks, ; Lu, Marks, & Apavaloaie, ; Marks & Chaney, ; Marks & Dollahite, ; Skipper, Marks, & Chaney, ). Participants reported that they were part of a church family or faith community that allowed them to serve others in need and also to be served when difficult circumstances arose.…”
Section: Generative Devotion Frameworkmentioning
confidence: 99%
“…(Brown, Lu, Marks, & Dollahite, ; Chaney et al, ; Dollahite, & Marks, ; Lu, Marks, & Apavaloaie, ; Marks & Chaney, ; Marks & Dollahite, ; Skipper, Marks, & Chaney, ). Participants reported that they were part of a church family or faith community that allowed them to serve others in need and also to be served when difficult circumstances arose.…”
Section: Generative Devotion Frameworkmentioning
confidence: 99%
“…Religion is a historically important coping mechanism among Black Americans, serving to mitigate the harsh consequences of discrimination and structural disadvantage (Taylor et al, ). So too, among Hispanics and Asians, does religion provide an ideological impetus for their relatively high degree of familism, serving to bond couples and their larger families as a unit (Bulanda & Brown, ; Lu, Marks, & Apavaloiae, ; Lu, Marks, & Baumgartner, ; Lu, Marks, Nesteruk, Goodman, & Apavaloaie, ; McLoyd et al, ). Drawing on deprivation theory , which suggests that religion is a particularly important coping and integrative force in the lives of economically marginalized groups (Lichter & Carmalt, ; Solt, Habel, & Grant, ), one would expect that spousal religiosity would exhibit a stronger, positive effect on marital outcomes for racial and ethnic minorities in the United States, relative to non‐Hispanic White Americans.…”
Section: Racial and Ethnic Identity Spousal Religiosity And Maritalmentioning
confidence: 99%
“…Research on religion and marriage has identified correlations between religious practice and enhanced marital quality, especially when those practices are shared [21]. Mahoney et al found that couples who pray for each other and attend religious services together seem to experience better marital quality [22].…”
Section: Religious Practices and Marriagementioning
confidence: 99%